U.S. CULTURE: DIVERSITY AND INTEGRATION - Azimjon Ahmedov; Rejapova Oydinoy (TADQIQOTLAR, 2026)
Abstract: This article presents a scholarly analysis of the cultural landscape of the United States, focusing on the dual processes of diversity and integration that have shaped the nation since its founding. Drawing on historical sources, demographic data, and sociological theory, the study examines how successive waves of immigration, indigenous heritage, and the legacy of slavery have produced one of the most heterogeneous societies in the modern world. The research applies qualitative content analysis and comparative-historical methods to evaluate the explanatory power of three competing models — the “melting pot,” the “salad bowl,” and contemporary multiculturalism — in describing American cultural reality. Findings indicate that no single model fully captures the complexity of U.S. society; rather, integration occurs through overlapping mechanisms including civic nationalism, economic mobility, public education, popular culture, and intermarriage, while distinct ethnic, religious, and regional identities continue to flourish. The article also addresses persistent challenges such as racial inequality, linguistic tensions, and political polarization. The conclusions suggest that American cultural identity is best understood as a dynamic equilibrium between unity and pluralism, in which the meaning of “American” is continuously renegotiated.